Targeting the CCL2/CCR2 Axis in Cancer Immunotherapy: One Stone, Three Birds? - Fei, Liyang; Ren, Xiaochen; Yu, Haijia; Zhan, Yifan (Frontiers in Immunology, 2021)
CCR2 is predominantly expressed by monocytes/macrophages with strong proinflammatory functions, prompting the development of CCR2 antagonists to dampen unwanted immune responses in inflammatory and autoimmune diseases. Paradoxically, CCR2-expressing monocytes/macrophages, particularly in tumour microenvironments, can be strongly immunosuppressive. Thus, targeting the recruitment of immunosuppressive monocytes/macrophages to tumours by CCR2 antagonism has recently been investigated as a strategy to modify the tumour microenvironment and enhance anti-tumour immunity. We present here that beneficial effects of CCR2 antagonism in the tumour setting extend beyond blocking chemotaxis of suppressive myeloid cells. Signalling within the CCL2/CCR2 axis shows underappreciated effects on myeloid cell survival and function polarization. Apart from myeloid cells, T cells are also known to express CCR2. Nevertheless, tissue homing of Treg cells among T cell populations is preferentially affected by CCR2 deficiency. Further, CCR2 signalling also directly enhances Treg functional potency. Thus, although Tregs are not the sole type of T cells expressing CCR2, the net outcome of CCR2 antagonism in T cells favours the anti-tumour arm of immune responses. Finally, the CCL2/CCR2 axis directly contributes to survival/growth and invasion/metastasis of many types of tumours bearing CCR2. Together, CCR2 links to two main types of suppressive immune cells by multiple mechanisms. Such a CCR2-assoicated immunosuppressive network is further entangled with paracrine and autocrine CCR2 signalling of tumour cells. Strategies to target CCL2/CCR2 axis as cancer therapy in the view of three types of CCR2-expessing cells in tumour microenvironment are discussed.